Choice of Tax Base Revisited: Cash Flow vs. Prepayment Approaches to Consumption Taxation - Syed M. Ahsan; Panagiotis Tsigaris (Center for Economic Studies and ifo Institute (CESifo), 2003)
This paper re-examines the issues involved in the design of a direct tax on consumption, an idea that has received a fair degree of acceptance in the transition countries over the past decade (e.g., tax reforms in Croatia and Moldova). First we argue that on the subject of equivalence among a set of taxes, the only meaningful comparison is along the ex-ante concept of equivalence, and not ex-post. The latter as we shall see requires highly implausible, and often arbitrary, choice scenarios. We carry out the analysis in a variety of models starting with the two-period consumption-saving choice under full certainty. However, a good part of the discussion is carried out where the portfolio choice behaviour is embedded in an intertemporal savings model that has been widely discussed in the literature. We then take up more complete (and necessarily more complex) choice situations for examination. Indeed the first of two variations of the above is a model where individuals make work-leisure (for a given skill level) as well as the safe-risky asset choice. The last is of risky human capital choice, where the physical investment is restricted to a single non-risky asset. For the purposes of the paper, the models are very general, and the precise choice context is open to wider interpretations than how they are actually phrased. In spite of our preoccupation with the efficiency aspects, we are interested in other important issues of equity, and those of an administrative nature. But our remarks on the latter fronts are limited to the insight that we directly gain from the analytics.
Keywords: 330; tax reform in transition countries; cash-flow tax; prepayment tax; ex-ante and ex-post equity; risk sharing; and tax reform